Pemodelan Hubungan Muatan Atom Bersih dengan Aktivitas Senyawa Turunan Metronidazol Ariloksi sebagai Antikanker Payudara dengan Metode AM1 - Qory Sidwa Jufri; Fajriah Azra (Departemen Kimia FMIPA UNP, 2023)
An analysis study of the relationship between the net atomic charge modeling of 13 aryloxy metronidazole derivative compounds as anti-breast cancer has been carried out, which aims to obtain the net atomic charge value and the HKSA equation. The method used is the semi-empirical method of Austin Model 1 by performing geometry optimization. The best equation model selection is done by means of statistical correlation analysis and multilinear regression with the Backward. From the research results, model 1 is the best model with the equation LogIC50=-777.834+(146.644*qC2)+(434.317*qC5)+(1299.237*qN7)-(243.853*qO8)-(65.686*qC10)-(137.823 *qC11)+(66.348*qO12) Dengan n=7; R= 0.943; R2= 0.89; SE= 0.14774; Sig= 0.036; PRESS= 0.10914.